Long-Term Survival of Hintegra Revision Ankle Arthroplasty in 116 Patients. Issue 4 (November 2022) - Kvarda, Peter; Susdorf, Roman; Horn-Lang, Tamar; Peterhans, Ursina; Ruiz, Roxa; Hintermann, Beat
Category: Ankle; Ankle Arthritis; Hindfoot Introduction/Purpose: Total ankle replacement (TAR) became a popularly utilized surgical solution for end-stage ankle osteoarthritis (OA). Consequent to the increased number of primary implantations, failed ankles are evermore challenge for foot and ankle surgeons. Historically, if the ankle failed, salvage was preferably fusion. Nowadays however, maintenance of the ankle and hindfoot functionality is first and foremost for the expanded patient group. Despite revision arthroplasty has been described as a viable option, the available literature on long-term outcomes is scarce. The aim of this study was to investigate the long-term survival of revision ankle arthroplasty in a uniquely large cohort using the mobile-bearing HINTEGRA prosthesis. Methods: We conducted a single-center retrospective cohort study included 116 patients (117) ankles following revision ankle arthroplasty for failed primary TAR from July 2000 to March 2010. Survival analysis was performed. Clinical outcomes including pain on visual analog scale (VAS), American Foot and Ankle Ankle-Hindfoot Score (AOFAS), ankle range of motion (ROM), and patient`s satisfaction were assessed preoperatively and at the last follow-up. Results: The mean follow-up time from initial revision arthroplasty to the latest follow-up was 15.0+-3.0 years (range 11.2 - 20.5). The cumulative survival of the revised ankles at 5, 10 and 15 years was 81+-4%, 74+-4%, and 70+-4%, respectively. Clinical outcomes including pain on VAS declined from median 6 (0 - 10) to 2 (0 - 10) (p<.0001)), and the AOFAS ankle-hindfoot score improved from 43+-17 to 70+-20 (p<.0001)) from preoperatively to the last follow-up. Conclusion: Despite difficult surgical challenge, revision ankle arthroplasty yields an acceptable survival rate and results on long- term, however lower than primary TAR. Careful preoperative planning is crucial to achieve the desired results. Fusion is may not anymore the state-of-the-art solution for failed ankles. The study provides unique information for foot and ankle surgeons improving patient-care and possibly influence decision-making process.